Legal Ownership of Images Generated by Generative Artificial Intelligence : (A Study of Buying and Selling Transactions on Adobe Stock in Indonesia) - Alisya Rahma Saebani; Heru Sugiyono; Muthia Sakti (Green Social: International Journal of Law and Civil Affairs, 2025)
The development of Artificial Intelligence (AI) technology has led to the creation of various works, including images generated without direct human involvement. One of the platforms that facilitates the buying and selling of AI-generated images is Adobe Stock. However, this raises legal issues regarding ownership status and copyright protection of such images, considering that Indonesia's positive law has not explicitly regulated ownership of works produced by non-human entities. This research aims to examine the legality of ownership over images generated by Generative AI in transactions through Adobe Stock and to analyze its compatibility with the Indonesian legal system. This study uses a normative juridical method with statutory, case, comparative, and conceptual approaches, as well as a literature study relevant to the issues discussed. The results show that under the Indonesian legal system, a work must have a creator who is a legal subject. Therefore, images generated by AI cannot automatically be granted copyright status unless there is significant human intervention in the creation process. In transactions through Adobe Stock, the platform's policy serves as the main reference in determining ownership and legal responsibility over AI-generated images. The legality of AI-generated image ownership in Indonesia remains a gray area and requires regulatory updates to accommodate technological developments. Legal clarity is needed to protect parties involved in AI-based digital transactions and to ensure legal certainty in the protection of creative works.